Pengaruh strategi metakognitif dalam pembelajaran berbasis masalah terhadap pencapaian hasil belajar fisika siswa kelas XI SMAN 4 Padang - Aulya Chasovy; Asrizal Asrizal (Universitas Negeri Padang, 2019)
The 21st century requires students to have various skills. The Indonesian government seeks to meet these needs through the 2013 Curriculum. In addition, the government also seeks to improve student learning outcomes through Integrated Science learning in Junior High School. The real conditions in the field indicate that the integrated science learning outcomes of students are still relatively low. One alternative solution to solve this problem is to implement an integrated science worksheet with scientific literacy. The purpose of this research was to investigate the effect of the application of Integrated Science Science Worksheets on Our Digestive Health Themes on the learning outcomes of Class VIII students of Junior High School No. 25 Padang. This type of research is a quasi-experimental research design with Posttest-Only Nonequivalent Control Group Design. The sampling technique used is purposive sampling and cluster random sampling. The instrument for collecting data in this research consisted of written test sheets for aspects of knowledge, attitude observation sheets for attitude aspects and performance assessment sheets for skills aspects. Data from the research were analyzed using descriptive statistics and a comparison of two averages. Based on the data analysis of the application of the Integrated Science Science Worksheet on Our Digestive Health Theme, we can conclude the results of the research. The results of hypothesis testing indicate that there are significant differences between the learning outcomes of students who use Integrated Science LKS and those who do not use it. This means that Integrated Science LKS has an effect on three aspects of learning outcomes of Class VIII students of Junior High School No. 25 Padang. The three aspects of learning outcomes are knowledge aspects, skill aspects, and attitude aspects. Integrated Science LKS has an influence at a 95% confidence level.